Effect of Different Protein and Protein-Energy Ratio in Diet on Growth of Common Carp (Cyprinus carpio) Fingerling - M. Setiawati; R. Sutajaya; M. Agus Suprayudi (Jurnal Akuakultur Indonesia)
Aquaculture activity including culture of common carp (Cyprinus carpio) is now facing on high price of feed.  Feed cost can reach more than 50% of production cost so that increase in feed price decreases in farmer benefit. Toward increasing in benefit, it needs efficiency on production cost.  This can be achieved by using a diet containing suitable protein and protein-energy ratio for the need of fish cultured.  Diet containing different protein levels (28% and 31%) and protein-energy ratios (8 and 10), and a commercial feed as a control were compared to determine protein content and protein-energy ratio suitable for common carp fingerlings.  The results showed that food efficiency was differed among the treatments, while relative growth rate was similar.  Diet containing protein of 31.15% with protein-energy ratio of 7.81, and protein of 28.08% with protein-energy ratio of 9.12 were resulting higher food efficiency compared to that of diet containing 31.15% protein with 7.81 protein-energy ratio and 28.27% protein with 8.28 protein-energy ratio.